(untitled) (Solukhumbu Multiple Campus Research Journal, 2023)
The present study entitled Teachers’ Motivational Factors and Student Learning Achievements tries to identify the factors responsible for low and high motivation of teachers and to investigate how far the teachers’ motivational factor affects students learning achievements. I used qualitative research method and narrative design as a research methodology and unstructured interview as tool for data collection. The participants were 5 secondary level teachers of Solukhumbu district taken through purposive non-random sampling procedure. The findings were workload management, remuneration, recognition, accountability, career development, institutional environment, availability of resources, administrative efficacy, opportunities for professional growth, and autonomy. The study emphasizes the pivotal role of motivation in creating a positive classroom environment, enhancing instructional effectiveness, and providing personalized attention to students. Ultimately, motivated teachers serve as inspirational role models, fostering student engagement and driving improved learning outcomes. The implications included practical training should be given to the teachers for updating contemporary skills.